2015
DOI: 10.1007/s10758-015-9254-8
|View full text |Cite
|
Sign up to set email alerts
|

Online Graduate Teacher Education: Establishing an EKG for Student Success Intervention

Abstract: Predicting which students enrolled in graduate online education are at-risk for failure is an arduous yet important task for teachers and administrators alike. This research reports on a statistical analysis technique using both static and dynamic variables to determine which students are at-risk and when an intervention could be most helpful during a semester. Time-series clustering analysis of online teacher education classes revealed that prediction is possible after the 10th week capturing over 78 % of at-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The longer a student has been in school, the more likely he or she is to complete a degree (Hart, 2012;Levy, 2007;Moore & Kearsley, 2005;Wang & Newlin, 2002). Several studies found grade point average (GPA) to be positively correlated with success in individual courses (Aragon & Johnson, 2008;Campbell, DeBlois, & Oblinger, 2007;Dupin-Bryant, 2004;Harrell & Bower, 2011;Hart, 2012;Jayaprakash, Moody, Laura, Regan, & Baron, 2014;Menager-Beeley, 2001;Morris, Wu, & Finnegan, 2005;Muse, 2003;Osborn, 2001;Shelton, Hung, & Baughman, 2015;Valasek, 2001). Some of these studies also found that both the verbal and mathematic scores on the SAT are strong predictors of academic success Cortes, 2013;Morris et al, 2005 Reason, 2003;Swail (2004) Blacks, Hispanics, Native Americans less likely to persist success on a more general level finding that academic performance in higher education mirrors that of previous academic experiences.…”
Section: Academic Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The longer a student has been in school, the more likely he or she is to complete a degree (Hart, 2012;Levy, 2007;Moore & Kearsley, 2005;Wang & Newlin, 2002). Several studies found grade point average (GPA) to be positively correlated with success in individual courses (Aragon & Johnson, 2008;Campbell, DeBlois, & Oblinger, 2007;Dupin-Bryant, 2004;Harrell & Bower, 2011;Hart, 2012;Jayaprakash, Moody, Laura, Regan, & Baron, 2014;Menager-Beeley, 2001;Morris, Wu, & Finnegan, 2005;Muse, 2003;Osborn, 2001;Shelton, Hung, & Baughman, 2015;Valasek, 2001). Some of these studies also found that both the verbal and mathematic scores on the SAT are strong predictors of academic success Cortes, 2013;Morris et al, 2005 Reason, 2003;Swail (2004) Blacks, Hispanics, Native Americans less likely to persist success on a more general level finding that academic performance in higher education mirrors that of previous academic experiences.…”
Section: Academic Factorsmentioning
confidence: 99%
“…How the data is used, and what actions are taken, depends on the needs of the group, and their placement in the hierarchy of the educational process (Jayaprakash et al, 2014;Shelton et al, 2015). Learning analytics data are used in three areas: descriptive, predictive, and prescriptive analyses (Affendey, Paris, Mustapha, Sulaiman, & Muda, 2010;Brown, 2011).…”
Section: Uses Of Datamentioning
confidence: 99%
See 2 more Smart Citations